2002
DOI: 10.22358/jafs/67903/2002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of processing temperature on chemical composition of solar-dried blood meal and on performance of broiler chickens

Abstract: An experiment was conducted to ascertain the optimum temperature for cooking (pre-heating) raw blood before solar drying. Raw blood was subjected to three cooking temperatures (50°, 70° and 90°C) for 30 min before solar drying at a temperature range from 45° to 56°C. In a feeding trial, four hundred and eighty 14-day-old broiler chickens were randomly allocated to four groups. The dietary treatments consisted of the control diet, which contained fish meal and soyabean meal as the main protein sources, and thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Blood meal can be included in poultry and swine diets up to a level of 25% ( Hazarika, 1994 ). Previous reports have indicated that inclusion of 1–4% blood meal in diet can improve poultry performance ( Anang et al., 2001 , Nuarautelli et al., 1987 ), while others show no adverse effect of higher levels of dietary blood meal on chicken growth ( Donkoh et al., 2002 , Khawaja et al., 2007 ). However, Castelló et al.…”
Section: Role Of Special Protein Products In Poultry Nutritionmentioning
confidence: 99%
“…Blood meal can be included in poultry and swine diets up to a level of 25% ( Hazarika, 1994 ). Previous reports have indicated that inclusion of 1–4% blood meal in diet can improve poultry performance ( Anang et al., 2001 , Nuarautelli et al., 1987 ), while others show no adverse effect of higher levels of dietary blood meal on chicken growth ( Donkoh et al., 2002 , Khawaja et al., 2007 ). However, Castelló et al.…”
Section: Role Of Special Protein Products In Poultry Nutritionmentioning
confidence: 99%
“…which are part of a slaughtered animal obtained from rendering operations (Meat and bone offal, blood, bones, intestines, rumen content, rejected carcasses of animals/poultry, milk and dairy processing wastes, fish and fish processing waste, earthworm meal, black soldier fly larvae meal, snail meal, poultry litter, hatchery wastes meal, locusts meal, dung beetle meal, single cell proteins, insect meal, meal worm scales, fungi meal, algae meal etc. are potentially used in poultry nutrition (Hazarika, 1994;Konwar and Barman, 2005;Denton et al, 2005;Abbas et al, 2020a;Abbas et al, 2020b;Abbas et al, 2020c;Arshad et al, 2022;Arshad et al, 2022a). Blood meal has been reported to be included in poultry feeds up to 25% level (Hazarika, 1994).…”
Section: Exploring the Diversity Of Protein Sources And Precise Formu...mentioning
confidence: 99%
“…Drying of blood requires high cost equipment coupled with facilities for central blood collection, which may be unaffordable and/or not applicable because the abattoir structure in Nigeria exists as smallscattered units. Moreover, previous work with blood involving sun drying in the development of alternative feedstuffs for poultry reported a long drying time of about three days (Adeniji 1995;Donkoh et al 2002;Odunsi et al 2004). However, previous studies by Sonaiya (1988) suggested the use of crop by-product materials as absorbents for blood in order to increase the surface area for quicker sun drying.…”
Section: Introductionmentioning
confidence: 99%